Veering in hemi-Parkinson's disease: Primacy of visual over motor contributions. (October 2015) - Ren, Xiaolin; Salazar, Robert; Neargarder, Sandy; Roy, Serge; Ellis, Terry D.; Saltzman, Elliot; Cronin-Golomb, Alice
Highlights: Direction of veering in Parkinson's disease (PD) depends on the side of PD onset. Veering in PD corresponds to the side of spatial bias, not motor bias. Vision-based rather than or in addition to motor-based strategies may aid PD walking. Abstract: Veering while walking is often reported in individuals with Parkinson's disease (PD), with potential mechanisms being vision-based (asymmetrical perception of the visual environment) or motoric (asymmetry in stride length between relatively affected and non-affected body side). We examined these competing hypotheses by assessing veering in 13 normal control participants (NC) and 20 non-demented individuals with PD: 9 with left-side onset of motor symptoms (LPD) and 11 with right-side onset (RPD). Participants walked in a corridor under three conditions: eyes-open, egocentric reference point (ECRP; walk toward a subjectively perceived center of a target at the end of the corridor), and vision-occluded. The visual hypothesis predicted that LPD participants would veer rightward, in line with their rightward visual-field bias, whereas those with RPD would veer leftward . The motor hypothesis predicted the opposite pattern of results, with veering toward the side with shorter stride length. Results supported the visual hypothesis. Under visual guidance, RPD participants significantly differed from NC, veering leftward despite a shorter right- than left-stride length, whereas LPD veered rightward (not significantly different from NC), despite shorter left- than right-stride length. LPD participants showed significantly reduced rightward veering and stride asymmetry when they walked in the presence of a visual landmark (ECRP) than in the eyes-open condition without a target. There were no group differences in veering in the vision-occluded condition. The findings suggest that interventions to correct walking abnormalities such as veering in PD should incorporate vision-based strategies rather than solely addressing motor asymmetries, and should be tailored to the distinctive navigational profiles of LPD and RPD.